2010
DOI: 10.1007/s00253-010-2451-4
|View full text |Cite
|
Sign up to set email alerts
|

Potential roles of anaerobic ammonium and methane oxidation in the nitrogen cycle of wetland ecosystems

Abstract: Anaerobic ammonium oxidation (anammox) and anaerobic methane oxidation (ANME coupled to denitrification) with nitrite as electron acceptor are two of the most recent discoveries in the microbial nitrogen cycle. Currently the anammox process has been relatively well investigated in a number of natural and man-made ecosystems, while ANME coupled to denitrification has only been observed in a limited number of freshwater ecosystems. The ubiquitous presence of anammox bacteria in marine ecosystems has changed our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
108
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 167 publications
(114 citation statements)
references
References 95 publications
1
108
0
2
Order By: Relevance
“…The low level of nitrite may be explained by a high turnover rate. It was hypothesized that n-damo bacteria cooperated with denitrifying bacteria which reduce nitrate to nitrite or with ammonium oxidizing bacteria (Hu et al 2011;Zhu et al 2010). In this case, the higher content of ammonium in lower sites suggested a high possibility of the cooperation between n-damo bacteria and ammonium oxidizing bacteria or archaea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low level of nitrite may be explained by a high turnover rate. It was hypothesized that n-damo bacteria cooperated with denitrifying bacteria which reduce nitrate to nitrite or with ammonium oxidizing bacteria (Hu et al 2011;Zhu et al 2010). In this case, the higher content of ammonium in lower sites suggested a high possibility of the cooperation between n-damo bacteria and ammonium oxidizing bacteria or archaea.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study showed that the population of n-damo bacteria can still grow in a natural environment after water flooding for a long time creating anoxic conditions. It was hypothesized that n-damo bacteria depend on redox gradients at oxic-anoxic interfaces in their natural environments (Zhu et al 2010). In addition, our results showed that the anaerobic condition and availability of ammonium would be of great significance to n-damo bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The n-damo is predicted to occur near the oxic-anoxic interface, having low concentrations of oxidizable substrates other than methane, as well as low level of sulfate and high level of nitrate (16). Such conditions prevail in anoxic wetlands (17). To date, however, there have been no reports of direct evidence for the occurrence of n-damo in wetlands.…”
mentioning
confidence: 91%
“…Extracted DNA was then examined using 1.0% agarose gel electrophoresis. The 16S rRNA and pmoA genes of M. oxyfera-like bacteria were amplified using nested PCR protocols as previously described (17,32). Detailed information on the primers used is provided in Table S2.…”
Section: Methodsmentioning
confidence: 99%
“…The littoral buffer zone harbors a changing environment between land and water, which suggests a complex microbial nitrification (Zhu et al, 2010. However, knowledge about the ammonia oxidizing communities in the littoral buffer zone remains unclear, but is essential for us to understand the N cycle.…”
Section: Introductionmentioning
confidence: 99%